Evaluation of the Widas River in Nganjuk Regency using the Pollutant Index Method - Ananda Chandra Suryarani; Riniwati, Harsuko; Wahyudi, Setyo Tri; Romadhon, Dimas Iqbal (Graduate School of Universitas Brawijaya, 2026)
The existence of water plays an important role in the lives of all living creatures. Water distribution on the earth’s surface is divided into sea water and fresh water. Rivers are an example of surface fresh water that provides a water source for life. Water quality plays a role in determining a river’s quality status and designation. The Widas River is a sub-watershed of Brantas located in Nganjuk Regency. Based on Government Regulation 61 of 2010, the Widas River is included in class II for the river category. The research was carried out to assess the water quality and quality status of the Widas River. The method used in descriptive-quantitative was obtained by applying the pollutant index method. Water quality data shows that the Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) parameters exceed the established class II quality standards, namely 3 mg/L for the eiver category. Meanwhile, the Widas River’s quality status, with a value of 2,22 using class II quality standards and 1,28 using class III quality standards, is included in the lightly polluted category. Meanwhile, with a value of 0.75 using class IV quality standards, it is included in the river category with good content. Based on this, class III quality standards in Government Regulation Number 2 of 2021 are more appropriate for the Widas River, Nganjuk Regency. Keywords: Pollutant Index, Quality Status of River, Water Quality, Widas River